2009
DOI: 10.1056/nejmoa0902579
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Improvement after Bevacizumab in Patients with Neurofibromatosis Type 2

Abstract: BACKGROUND Profound hearing loss is a serious complication of neurofibromatosis type 2, a genetic condition associated with bilateral vestibular schwannomas, benign tumors that arise from the eighth cranial nerve. There is no medical treatment for such tumors. METHODS We determined the expression pattern of vascular endothelial growth factor (VEGF) and three of its receptors, VEGFR-2, neuropilin-1, and neuropilin-2, in paraffin-embedded samples from 21 vestibular schwannomas associated with neurofibromatosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
306
2
11

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 441 publications
(328 citation statements)
references
References 30 publications
9
306
2
11
Order By: Relevance
“…Neurofibromatosis 2, a rare genetic disease defined by a defect in a single allele of the Nf2 gene (and hence loss of its product, the tumor suppressor merlin) often presents with bilateral acoustic neuromata, which compress the vestibular nerve causing deafness and other complications relating to their expansion in the cerebellopontine angle (Lu-Emerson and Plotkin 2009). Vessel tortuosity Bullitt et al 2007 Vestibular schwannomas are known to express VEGF and VEGFRs, and the VEGF level within these tumors correlates with their growth rate (Brieger et al 2003;CayeThomasen et al 2003CayeThomasen et al , 2005Plotkin et al 2009). Interestingly, the mechanism of heightened VEGF activity in these tumors is not hypoxia-driven VEGF overexpression, but rather a loss of factors that attenuate VEGF function.…”
Section: Benign Tumorsmentioning
confidence: 99%
“…Neurofibromatosis 2, a rare genetic disease defined by a defect in a single allele of the Nf2 gene (and hence loss of its product, the tumor suppressor merlin) often presents with bilateral acoustic neuromata, which compress the vestibular nerve causing deafness and other complications relating to their expansion in the cerebellopontine angle (Lu-Emerson and Plotkin 2009). Vessel tortuosity Bullitt et al 2007 Vestibular schwannomas are known to express VEGF and VEGFRs, and the VEGF level within these tumors correlates with their growth rate (Brieger et al 2003;CayeThomasen et al 2003CayeThomasen et al , 2005Plotkin et al 2009). Interestingly, the mechanism of heightened VEGF activity in these tumors is not hypoxia-driven VEGF overexpression, but rather a loss of factors that attenuate VEGF function.…”
Section: Benign Tumorsmentioning
confidence: 99%
“…The report of a favorable impact of an anti-angiogenic treatment on hearing in NF2 VS patients compels the need to understand the relationship between VS growth and hearing loss [16]. As a result, hearing outcome during treatment has became the primary endpoint for clinical trials investigating antiangiogenic compounds such as bevacizumab.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the use of anti-angiogenic drug therapy has suggested a beneficial effect on hearing, an endpoint that is overlooked in the preclinical field [16]. Thus, a better understanding of the process underlying hearing loss requires specific models.…”
Section: Introductionmentioning
confidence: 99%
“…16 Several studies have also indicated that VEGF and VEGFR antagonists have roles in the treatments of other brain tumors, including vestibular schwannomas, meningiomas, and low-grade astrocytomas. 5,[7][8][9]11,12,17,18 Despite being nonmalignant brain tumors, vestibular schwannomas and meningiomas carry significant morbidity and risk of mortality for certain patients. Many but not all of these tumors can be treated with surgery or radiotherapy.…”
Section: Discussionmentioning
confidence: 99%